The role of breastfeeding as a protective factor against the development of the immune-mediated diseases: A systematic review - Alotiby, Amna A. (Frontiers in Pediatrics, 2023)
Breast milk is rich in nutrients and immunological factors capable of protecting infants against various immunological diseases and disorders. The current systematic review has been framed with the objective of studying the role of breastfeeding as a protective factor against the development of immune-mediated diseases. The database and website searches were performed using PubMed, PubMed Central, Nature, Springer, Nature, Web of Science, and Elsevier. The studies were scrutinized based on the nature of participants and the nature of disease considered. The search was restricted to infants with immune-mediated diseases such as diabetes mellitus, allergic conditions, diarrhoea, and rheumatoid arthritis. We have included 28 studies, out of which seven deal with diabetes mellitus, two involving rheumatoid arthritis, five studies about Celiac Disease, twelve studies about allergic/asthma/wheezing conditions and one study on each of the following diseases: neonatal lupus erythematosus and colitis. Based on our analysis, breastfeeding in association with the considered diseases was found to be positive. Breastfeeding is involved as protective factor against various diseases. The role of breastfeeding in the prevention of diabetes mellitus has been found to be significantly higher than for other diseases.